1992
DOI: 10.1177/0022022192232005
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Individualism Collectivism, Self-Monitoring, and Predicted-Outcome Value on Communication in Ingroup and Outgroup Relationships

Abstract: This study examined the influence of individualism-collectivism on communication in ingroup and outgroup relationships. Differences were predicted in ingroup and outgroup communication in collectivistic cultures. It was also hypothesized that self-monitoring and predicted-outcome value (POV) of the relationships also affect communication processes in these relationships. Data were collected in Hong Kong and Japan (collectivistic) and in Australia and the United States (individualistic). Results supported the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(68 citation statements)
references
References 21 publications
3
61
0
Order By: Relevance
“…This may also be relevant to studies which have found that the social relationship between the observer and the performer may influence mirror neuron activity (Liew, Han, & Aziz-Zadeh, 2010). The reward value attributed to the observed action can depend upon the relationship between confederates in a social interaction, such as that demonstrated by in-group vs. out-group differences (Gudykunst et al, 1992;Sobhani, Fox, Kaplan & Aziz-Zadeh, 2012), and competitive vs. cooperative scenarios (Koban, Pourtois, Vocat, & Vuilleumier, 2010). Different social contexts will induce different degrees of reward associated with others' actions, which could depend upon a wide variety of personal and interpersonal motivational factors.…”
Section: Discussionmentioning
confidence: 90%
“…This may also be relevant to studies which have found that the social relationship between the observer and the performer may influence mirror neuron activity (Liew, Han, & Aziz-Zadeh, 2010). The reward value attributed to the observed action can depend upon the relationship between confederates in a social interaction, such as that demonstrated by in-group vs. out-group differences (Gudykunst et al, 1992;Sobhani, Fox, Kaplan & Aziz-Zadeh, 2012), and competitive vs. cooperative scenarios (Koban, Pourtois, Vocat, & Vuilleumier, 2010). Different social contexts will induce different degrees of reward associated with others' actions, which could depend upon a wide variety of personal and interpersonal motivational factors.…”
Section: Discussionmentioning
confidence: 90%
“…The values and behaviors typically associated with Asian Americans include (a) collectivism or being group oriented (Gudykunst et al , 1992), (b) deference to authori ty (S ue, 1989), and (c) keeping fam ily conflicts within the family (Sue, 1989). Along with cultural values, acculturation is another salient issue in Asian…”
Section: Cultural Considerations When Counseling Asian American Menmentioning
confidence: 99%
“…This evidence supports the interdependence between cultural practices, psychological structures and discourse processes. In brief, cultural variability has a major effect on social norms, roles, self-constmal, language usage, and above all, discursive styles (Gudykunst et al, 1992;Gudykunst et al, 1996, Ting-Toomey et al, 1991. The interconnections between situational factors, social cognitive processes, affect, and behaviours (e.g., habits) have an impact on the intentions and understanding of communications (Gudykunst et al, 1988).…”
Section: A Ck N O W Led G Em En Tsmentioning
confidence: 99%
“…Research regarding intercultural differences in information seeking strategies have shown that people in high-context cultures are more cautious in initial interactions, rely more on nonverbal expressiveness, make more assumptions and ask more questions about the other's background (Baldwin & Hunt, 2002;Gudykunst et al, 1992;Gudykunst et al, 1996).…”
Section: A Ck N O W Led G Em En Tsmentioning
confidence: 99%
See 1 more Smart Citation